A numerical study of diurnally varying surface temperature on flow patterns and pollutant dispersion in street canyons. (March 2015) - Tan, Zijing; Dong, Jingliang; Xiao, Yimin; Tu, Jiyuan
Abstract: The impacts of the diurnal variation of surface temperature on street canyon flow pattern and pollutant dispersion are investigated based on a two-dimensional street canyon model under different thermal stratifications. Uneven distributed street temperature conditions and a user-defined wall function representing the heat transfer between the air and the street canyon are integrated into the current numerical model. The prediction accuracy of this model is successfully validated against a published wind tunnel experiment. Then, a series of numerical simulations representing four time scenarios (Morning, Afternoon, Noon and Night) are performed at different Bulk Richardson number ( Rb ). The results demonstrate that uneven distributed street temperature conditions significantly alters street canyon flow structure and pollutant dispersion characteristics compared with conventional uniform street temperature assumption, especially for the morning event. Moreover, air flow patterns and pollutant dispersion are greatly influenced by diurnal variation of surface temperature under unstable stratification conditions. Furthermore, the residual pollutant in near-ground-zone decreases as Rb increases in noon, afternoon and night events under all studied stability conditions. Highlights: Uneven street temperature condition is used to model surface heating effects. Significant differences are observed compared with conventional uniform assumption. Air pollution inside street canyons is closely linked with thermal stratification.